Use of restrictive interventions in a child and adolescent inpatient unit – predictors of use and effect on patient outcomes. (August 2014) - Duke, Suzanne G; Scott, James; Dean, Angela J
Objectives: Restrictive interventions (seclusion, physical restraint, and use of acute/p.r.n. sedation) may have negative effects on patients. Identifying factors associated with use of restrictive interventions and examining their effect on admission outcomes is important for optimising inpatient psychiatric care. Methods: This study documented use of restrictive interventions within a child and adolescent psychiatric inpatient unit for 15 months. Two models examined predictors of use of restrictive interventions: (i) incident characteristics; and (ii) patient characteristics. The relationship between use of restrictive interventions and global clinical outcomes was also examined. Results: Of 134 patients admitted during the study period (61.9% female, mean age=13.8±2.9 years), 26.9% received at least one restrictive intervention. Incident factors associated with restrictive interventions were: physical aggression, early admission stage, and occurrence in private space. Patient factors that predicted use of restrictive interventions were developmental disorder and younger age. Use of restrictive interventions was not associated with increased length of stay or diminished improvement in global symptom ratings. Conclusions: Further research is needed to identify best practice in children at high risk for receiving restrictive interventions.